The Effectiveness of the Thumb Sakera Program in Pasuruan Regency - Mursyidah, Lailul; Rodiyah, Isnaini; Agustina, Isna Fitria; Setiawan, Ikhsan; Rustianingsih, Eni (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2023)
The Office of Family Planning and Women's Empowerment created an innovation to reduce the number of women's violence in Pasuruan Regency. The program is the Thumb Sakera program (Aware of the Violence of Women and Children by Picking Up Balls). The purpose of this study was to describe and analyze the innovation of the Thumb Sakera program (Aware of the Violence of Women and Children by Picking Up Balls) in Pasuruan Regency. This study uses a quantitative descriptive. The sample of this research is 32 people. Data processing techniques use statistical analysis which consists of grouping data based on respondents, tabulating data based on all respondents, presenting data according to research results, and carrying out calculations to answer the problem formulation. The analysis technique used is the Likert scale technique. The results of the validity test of this study showed that Cronbach's Alpha was above 0.6 which means that each item was declared valid. In addition, the reliability test of 12 items shows a strong reliability with Cronbach's Alpha 0.764. It can be identified that the results of the research on the effectiveness of the Thumb Sakera program in Pasuruan Regency are in the "Effective" category. The average value is 78.59% which is obtained from the determination indicator; program target of 82.29%; program socialization of 75.84%; program objectives of 79.59; and program monitoring of 76.67%.